Ivan Rosenberg. Issue 37 (1st October 2018) - Unknown
Abstract: "The Rosenberg group is interested in the area of nucleic acids chemistry." Find out more about this author's research athttps://doi.org/10.1002/ejoc.201800490 . Abstract : "The Rosenberg group is interested in the area of nucleic acids chemistry." Find out more about this author's research athttps://doi.org/10.1002/ejoc.201800490 .